Reducing Bits in Electrodeposition Process of Commercial Vehicle - A Case Study - Nabiilah, Ab Rahim; Zamzuri, Hamedon; Faiz, Mohd Turan; Ismed, Iskandar (IOP Publishing, 2016)
Painting process is critical in commercial vehicle manufacturing process for protection and decorative. The good quality on painted body is important to reduce repair cost and achieve customer satisfaction. In order to achieve the good quality, it is important to reduce the defect at the first process in painting process which is electrodeposition process. The Pareto graph and cause and effect diagram in the seven QC tools is utilized to reduce the electrodeposition defects. The main defects in the electrodeposition process in this case study are the bits. The 55% of the bits are iron filings. The iron filings which come from the metal assembly process at the body shop are minimised by controlling the spot welding parameter, defect control and standard body cleaning process. However the iron filings are still remained on the body and carry over to the paint shop. The remained iron filings on the body are settled inside the dipping tank and removed by filtration system and magnetic separation. The implementation of filtration system and magnetic separation improved 27% of bits and reduced 42% of sanding man hour with a total saving of RM38.00 per unit.